Effective body positions for rotations about the longitudinal axis - An example in figure skating jumps - Knoll, Ka.; Schüler, A.; Lehmann, T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
For successful quadruple jumps (QJ) in figure skating an extremely high angular velocity during the flight and a safe and clean landing on one foot are necessary. The moment of inertia (MOI) of the skater is a key factor of the angular velocity in the air. It is important to achieve the smallest MOI as fast as possible and to maintain it as long as possible. In this study seven different flight positions in three different phases of the flight have been identified, namely two positions in the phase from takedff to the closed position, three closed positions in the air and two positions in preparation for landing. Thus a method has been developed to identify individually best flight positions in QJ. Two closed flight positions were found as positions with the smallest M01, both with 17 Oh smaller MOI than the third closed flight position.